O profissional docente do ensino de Direito: o processo de construção de identidade e saberes docentes nas trajetórias de vida - Silva, Jozimeire Angélica Stocco de Camargo Neves da (2016)
The research The Professional Law Education Teacher: the identity building process and teaching knowledge during life trajectories is an investigation with professors who teach in the Graduate courses Sensu Lato, Law School of São Bernardo do Campo. The approach is about building identity and teaching knowledge of law professors during the trajectories of how they engage in teaching, without specific training, influenced by legal practice, as well as foregrounding the issues of training, professionalism and teaching procedure in these courses, contextualizing the Institution where the research took place and composing a frame of reference for reflection on the legal teaching. The study was conducted from the assumptions of the qualitative dimension, involving document analysis and reflective research through various procedures. In the focus of this study, we sought theoretical support from the authors that address the themes: Narratives of Life (Josso, 2007), Teacher Training in Contemporaneity (Feldmann, 2009; Novoa, 2000); Teacher Training (Nóvoa, 2000); Teaching Profession (Sacristán, 1998, 2000, 2013); Professionalization and Professionalism (Contreras, 2002; Tardiff 2012, 2014; Perrenoud 1999, 2002); Professor of Higher Education (Masetto, 2003, 2010, 2012 and 2013). We conclude that the teachers participating in this research have learned to be teachers and "are being it" in the trajectories that enabled the acquisition of knowledge and possible interaction with the student and the institution in which they work, and this can contribute to the construction of their identity process and that there is a collective identity of belonging to the mastership, even without training related to university teaching